2022
DOI: 10.3390/ijms23052655
|View full text |Cite
|
Sign up to set email alerts
|

A Redox-Silent Analogue of Tocotrienol May Break the Homeostasis of Proteasomes in Human Malignant Mesothelioma Cells by Inhibiting STAT3 and NRF1

Abstract: 6-O-Carboxypropyl-alpha-tocotrienol (α-T3E) is a multi-target redox-silent analogue of tocotrienol that exhibits cytotoxicity against many cancer cells, including malignant mesothelioma (MM) cells. α-T3E has several molecular targets to effectively induce cytotoxicity against MM cells; however, the mechanisms underlying this cytotoxicity remain unclear. In the present study, we demonstrated that the α-T3E-dependent disruption of the homeostasis of proteasomes strongly induced endoplasmic reticulum (ER) stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In another TNBC study, proteasome subunit cleavage site-specific inhibitor treatments and CRISPR/Cas9-mediated genetic inhibition of proteasome subunit cleavage site-suppressed NFE2L1 activity and mediated proteasome subunit induction, and prevented "bounce-back" effect in vitro and in vivo [124]. Six-O-carboxypropyl-αtocotrienol (α-T3E), a redox-silent analogue of tocotrienols, was shown to disrupt proteasome homeostasis by inactivating NFE2L1, eventually inducing severe ER stress and increasing the sensitivity of chemoresistance (cisplatin) in malignant mesothelioma cells [125].…”
Section: Resistance To Cell Deathmentioning
confidence: 99%
“…In another TNBC study, proteasome subunit cleavage site-specific inhibitor treatments and CRISPR/Cas9-mediated genetic inhibition of proteasome subunit cleavage site-suppressed NFE2L1 activity and mediated proteasome subunit induction, and prevented "bounce-back" effect in vitro and in vivo [124]. Six-O-carboxypropyl-αtocotrienol (α-T3E), a redox-silent analogue of tocotrienols, was shown to disrupt proteasome homeostasis by inactivating NFE2L1, eventually inducing severe ER stress and increasing the sensitivity of chemoresistance (cisplatin) in malignant mesothelioma cells [125].…”
Section: Resistance To Cell Deathmentioning
confidence: 99%
“…Subsequently, mTORC1 prompts NFE2L1 activation to enhance proteasome synthesis and ERAD [ 57 ]. Moreover, STAT3, another transcription factor promoting NFE2L1 expression, could be activated by both mTORC1 and ROS, thereby contributing to NFE2L1 induction under ER stress [ 14 , 125 ]. In addition, the nutrient-sensing pathway named AMPK signalling may antagonize NFE2L1 since AMPK can impede mTORC1 signalling by maintaining TSC1/2 activity [ 126 ].…”
Section: Nfe2l1 In Stress Responsesmentioning
confidence: 99%
“…Numerous novel studies have been performed on the regulatory molecules and pathways associated with NFE2L1 as a biomarker and therapeutic target in various tumors ( Table 1 ) [ 123 , 125 , [145] , [146] , [147] , [148] ]. The antioxidant stress response cascades mediated by NFE2L1 hold great promise as effective targets for tumour therapy, and the concurrent inhibition of proteasomes and NFE2L1 has been proven to enhance the therapeutic efficacy against malignancies.…”
Section: Nfe2li-mediated Diseases and Therapeutic Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…While vitamin E is well regarded as useful for cancer prevention due to its antioxidant effect, tocotrienols, a member of the vitamin E family, and redox-silent analogs of vitamin E such as α-tocopheryl succinate (TOS) and 6-O-Carboxypropyl-alpha-tocotrienol (T3E) are also known to exhibit anticancer effects via inhibition of specific cancer-related molecules such as HIF, Src, and STAT3 [22][23][24][25][26][27]. Furthermore, previous studies have reported that γ-tocotrienol and T3E modulate the expression levels of some proteasome-component proteins regulated by NFE2L1 [28,29]. Therefore, vitamin E and its redox-silent analogs may affect NFE2L1.…”
Section: Of 13mentioning
confidence: 99%